Robust control of single input multi outputs systems - D. Zehar; K. Behih; A. Cherif (Electrical engineering & Electromechanics)
Introduction. Most of mechanical systems are nonlinear and complex, the complexity of these latter lies on highly nonlinear characteristics, or on dynamics that stimulate the development or change of the process through an applied force in a disturbed environment. Single input multi outputs (SIMO) systems, which are structured into subsystems, are considered as complex systems. The task to control their degrees of freedom is more complicated, and it is not easily reachable, due to the fact that nonlinear laws are not directly applicable to those systems, which requires to trait them in a particular way. Problem. First order sliding mode control (FOSMC) has already been applied in several previous works to this kind of systems, and due to its robustness property, this control gave good results in term of stabilization and tracking, but the chattering phenomenon remains a big problem, which affects the control structure and the actuators. Purpose. In order to address the problem of chattering encountered when applying the FOSMC to a category of second order subsystems, a second order sliding mode control (SOSMC) is designed. Methods. This work consists of developing an appropriate second order system structure, which can go with the sliding control expansion, and then studying the SOSMC for this chosen system. The hierarchical structure of the sliding surface which is made using a linear combination between subsurfaces, according to the system structure, allows the only control input to affect subsystems in graded manner from the last one to the first one. Results. We have applied the constructed control law to a SIMO system for two cases with and without disturbances. Simulation results of the application have shown the effectiveness and the robustness of the designed controller. References 30, figures 10.